The Effect of GeoGebra-Assisted E-Modules on Students' Ability to Solve Problems Mathematically - Arvin Efriani; Sujinal Arifin; Salsabila, Nanda (JMPM: Jurnal Matematika dan Pendidikan Matematika, 2025)
This research implements a posttest-only control group experimental design to examine the impact of a GeoGebra-integrated e-module on students' mathematical problem-solving abilities. A sample of 68 eighth-grade learners at SMP Negeri 57 Palembang participated in the study, divided into experimental and control groups. The experimental group utilized an interactive e-module featuring GeoGebra software integration, while the control group received conventional instruction. The results showed that students who used the e-module achieved significantly better outcomes in problem recognition, strategy development, implementation of solutions, and outcome assessment. The mean posttest results obtained by the experimental group were higher than those of the control group. A t-test confirmed a statistically significant difference between the two groups. Based on statistical analysis, integrating GeoGebra within a structured digital module demonstrates potential to strengthen students' conceptual understanding, engagement, and problem-solving skills, especially in learning straight-line equations. Furthermore, the approach promotes higher-order thinking and learner autonomy, offering a promising strategy for improving mathematics instruction at the junior high school level.